2015
DOI: 10.1111/apm.12391
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Chlamydia trachomatis, Ureaplasma urealyticum and Mycoplasma hominis in infertile Bulgarian men with multiplex real‐time polymerase chain reaction

Abstract: The effect of Chlamydia trachomatis, Ureaplasma urealyticum and Mycoplasma hominis over the sperm quality is still unclear. The aim of this study was to determine their prevalence in infertile Bulgarian men. A total of 281 men were examined by applying mRT-PCR. The registered prevalence was as follows: C. trachomatis - 13.9%, U. urealyticum - 19.2%, M. hominis - 9.9%. Co-infection was established in eight swabs. This first in Bulgaria to study for detection of chlamydia and mycoplasmas in infertile men by mRT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…However, UU, CT, and MG are difficult to be diagnosed by routine microscopic examination of vaginal or cervical secretions. Mycoplasma and chlamydia are also difficult to be identified by microbial culture due to their slow growth and high nutrient requirements [ 15 , 16 ]. In particular, the culture of MG in clinical specimens is more difficult to succeed [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, UU, CT, and MG are difficult to be diagnosed by routine microscopic examination of vaginal or cervical secretions. Mycoplasma and chlamydia are also difficult to be identified by microbial culture due to their slow growth and high nutrient requirements [ 15 , 16 ]. In particular, the culture of MG in clinical specimens is more difficult to succeed [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Male infertility is mostly caused by STDs; a high titre of seropositive Chlamydia antibodies, which is a marker of severe infection, has been found to be associated with male infertility [ 70 ]. There was a significant increase in the number of Chlamydia -, Mycoplasma hominis -, and Ureaplasma urealyticum -positive PCR results in infertile men as compared with fertile men, demonstrating that there is a strong link between STD infection and infertility [ 71 ]. When spermatozoa were incubated with lipopolysaccharides isolated from Chlamydia , the results showed that the spermatozoa died completely and that their motility had decreased [ 72 ].…”
Section: Causes Of Inflammation In Male Reproductive Tractmentioning
confidence: 99%
“…Semen Sperm concentration, motility and morphology were significantly reduced in CT patients; strong correlation between mucosal anti– CT IgA and sperm concentration, sperm motility, and normal morphology Case-control [ 61 ] 60 IM, 40 healthy controls. Urethral swabs from IM No significant difference in CT prevalence between IM & FM Case-control [ 62 ] 281 IM; 100 fertile controls. Semen PCR detected CT in 13.9% of IM vs 2% of FM Case-control [ 63 ] 135 IM, 88 FM Blood, semen, urethral smears No significant difference in CT prevalence between IM & FM Cross-sectional [ 64 ] 29 subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Semen, Urine NG found in 6.5% of IM, 0 in FM ( p < 0.05) Case-control ( UU, MH ) [ 56 ] 621 IM; 615 FM Semen No significant difference in UU, MH prevalence between IM & FM; UU was related, in infected compared with uninfected men, to lower mean sperm concentration and lower vitality; No significant difference in semen parameters between MH +ve and -ve patients. Cross-Sectional ( MG, UU, NG ) [ 58 ] 2607 infertile men Semen, Urine DFI was significantly higher in UU and MG infected men compared to non-infected; No significant difference in other semen; No significant difference in all semen parameters between NG infected and not-infected groups Case-control ( MH, UU) [ 62 ] 281 IM; 100 fertile controls. Semen PCR detected UU & MH in 19.2% vs 11% & 9.9% vs 3% in IM vs FM, respectively Case-control ( MH, UU) [ 63 ] 135 IM, 88 FM Blood, semen, urethral smears Significant difference in prevalence of MH between FM and IM; No difference in prevalence if considering UU alone Cross-sectional ( UU, UP, MH, MG, NG ) [ 73 ] 195 infertile men.…”
Section: Resultsmentioning
confidence: 99%